Paulus se "godsdienspatroon" en die bepaling van verwysing - Engelbrecht, E. (Hervormde teologiese studies, 1986)
Paul's 'pattern of religion' and the determination of reference The interpretation of meaning in a Pauline text starts in the micro-context and proceeds via the macro-structure of the letter to Paul's pattern of religion. This implies a synchronic approach. It is argued that a pattern of religion thus constructed functions as a method of control in establishing an interpretation of meaning. Pattern of religion consists of that which is basic to Pauline thinking and the first phase surface motives which are generated by this basic pattern of belief. The study concludes that the interpretation of meaning in Paul should take note of the uniqueness of Paul's thinking. The method developed is pointed by an interpretation of the meaning of eleos in Romans 15:9.